2019
DOI: 10.1186/s12912-019-0362-y
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized patients’ pain experience before and after the introduction of a nurse-based pain management programme: a separate sample pre and post study

Abstract: Background Many patients suffer from unrelieved pain in hospital settings. Nurses have a pivotal role in pain management. Hence, a nurse-based pain management programme may influence how hospitalized patients experience pain. In this study we investigated hospitalized patients’ experience of pain before and after the introduction of a two-component nurse-based pain management programme. Methods A quasi-experimental design with a separate sample pretest-posttest approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
5
0
7
Order By: Relevance
“…Pain management education is important to optimise patient comfort, prevent under‐treatment of pain and reduce harmful effects of unrelieved pain. While ongoing education is effective in imparting knowledge and developing skills in pain management, there is little evidence of improved clinical performance and patient outcomes (Bloom, 2005; Germossa, Hellesø, & Sjetne, 2019; Sinclair, Kable, Levett‐Jones, & Booth, 2016). One recent study demonstrated marked reductions in the number of hospitalised patients ( n = 845) reporting moderate and severe pain (72.8% to 48.5), and interference in physical and emotional functions after introducing a nurse‐based pain management program comprising face‐to‐face education (30–40 min) and daily clinical rounding using scripted pain assessment dialogue (Germossa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain management education is important to optimise patient comfort, prevent under‐treatment of pain and reduce harmful effects of unrelieved pain. While ongoing education is effective in imparting knowledge and developing skills in pain management, there is little evidence of improved clinical performance and patient outcomes (Bloom, 2005; Germossa, Hellesø, & Sjetne, 2019; Sinclair, Kable, Levett‐Jones, & Booth, 2016). One recent study demonstrated marked reductions in the number of hospitalised patients ( n = 845) reporting moderate and severe pain (72.8% to 48.5), and interference in physical and emotional functions after introducing a nurse‐based pain management program comprising face‐to‐face education (30–40 min) and daily clinical rounding using scripted pain assessment dialogue (Germossa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While ongoing education is effective in imparting knowledge and developing skills in pain management, there is little evidence of improved clinical performance and patient outcomes (Bloom, 2005; Germossa, Hellesø, & Sjetne, 2019; Sinclair, Kable, Levett‐Jones, & Booth, 2016). One recent study demonstrated marked reductions in the number of hospitalised patients ( n = 845) reporting moderate and severe pain (72.8% to 48.5), and interference in physical and emotional functions after introducing a nurse‐based pain management program comprising face‐to‐face education (30–40 min) and daily clinical rounding using scripted pain assessment dialogue (Germossa et al, 2019). While nurse‐initiated analgesia is safe and effective (Cabilan & Boyde, 2017; Varndell et al, 2018), further research is required to examine education and knowledge translation modalities and their impact on patient‐orientated and clinical outcomes within the ED setting.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has also pointed out the importance of improving nurses' knowledge and attitude (20,21) and work process re-organization to produce a better outcome (22). However, to our knowledge, no investigation has been conducted to assess the impact of a nurse-based in-hospital pain care program on patients' experiences with pain care.…”
Section: Introductionmentioning
confidence: 99%
“…Para poder aplicar una estrategia terapéutica adecuada en el DAP tras cesárea, es fundamental llevar a cabo una exhaustiva evaluación del dolor, actividad que recae de forma central en los profesionales de la Enfermería (5,10,12,41,44,45,52,53,62,73,82,123,161,197,198). No puede entenderse su labor en el aporte de cuidados postoperatorios tras la cesárea sin una óptima valoración del dolor percibido por las pacientes y las repercusiones que este conlleva en el contexto de un abordaje de la salud biopsicosocial, como proponen los modelos de Enfermería vigentes y que rigen los principios de la disciplina como profesión (11,19,41,54,63,124,199).…”
Section: Discusión 1 Evaluación Del Dap En La Cesáreaunclassified
“…La prevalencia del DAP tras cesárea en nuestra muestra de estudio se mantiene en la línea de la aportada por la literatura científica, por ello, su manejo y control suponen un importante reto para todos los profesionales sanitarios implicados, con especial atención a los profesionales de la Enfermería, quienes tienen un papel central a través del desempeño de sus funciones a lo largo de todo el periodo postoperatorio, y para quienes constituye una prioridad (5,10,62,72,73,199).…”
Section: Limitaciones Del Estudio Y Perspectivas Futurasunclassified